Design of incentive systems : experimental approach to incentive and sorting effects - Fehrenbacher, Dennis D. (Contributions to Management Science, 2013)
Monetary incentives, as a driving force for human behavior, are the main theme of this book. The primary goals underlying the application of monetary incentive systems in companies are motivating employees to strive for superior productivity in line with the interests of employers, and hiring adequately skilled employees. The first goal refers to incentive effects, the latter to sorting effects. This book introduces important theories and concepts concerning behavior under influence of monetary incentives; it reviews existing economic frameworks and identifies specific contingency variables. Based on an integrative framework of elements influencing incentive and sorting effects, a laboratory experiment is presented including detailed methodological discussion on experimentation and data analysis as well as an extensive presentation of findings and discussion of implications.